Tendencies for the Development of Marriage Conflict Legal Regulation with the Participation of Foreigners and Persons without Citizenship in the Post-Soviet Space - Bodurova, Gulshan Gurezovna; Tagaeva, Sanavbar Nazirkulovna (Cuestiones Políticas, 2020)
The article describes trends in the development of legal regulation linked to collisions that regulate marriage matters under the laws of post-Soviet countries. At the methodological level it is a comparative research of documentary basis. It is noted that, despite the general historical development of legal institutions and ongoing harmonization, the regulation of the principles of marriage collision has its own peculiarities in the countries of the former Soviet Union. This trend is explained by the specific and heterogeneous regulation of marriage and family relations in the legislation of different countries. But in the context of integration processes, the displacement of people from one country to another, marriage and family relationships also tend to develop. The article provides comparative analysis of the vast material, especially regulatory legal acts of post-Soviet countries, which regulate marriage and family relations in order to identify common and special characteristics. They revealed trends in the regulation of marriage conflicts in post-Soviet countries, as well as the regulation of marriage disputes in a consular office or diplomatic mission.